LGG-40. EX VIVO TISSUE METABOLITE PROFILES PREDICT PROGRESSION-FREE SURVIVAL IN PAEDIATRIC CEREBELLAR PILOCYTIC ASTROCYTOMAS. Issue 2 (22nd June 2018) - Bennett, Christopher; Kohe, Sarah; Gill, Simrandip; Ghosh, Neelakshi; Manias, Karen; Oates, Adam; English, Martin; Adamski, Jenny; Tennant, Daniel; Peet, Andrew
Abstract: Pilocytic astrocytomas are the most common brain tumours arising in children, accounting for 18% of primary brain tumours. 42% are cerebellar in origin and, whilst they have an excellent 10-year overall survival rate of >90%, progression-free survival for these tumours is variable. Identifying tumours more likely to progress will help determine those requiring more aggressive treatment. Metabolite profiles were obtained from 23 cerebellar pilocytic astrocytomas using High Resolution Magic Angle Spinning NMR (HR-MAS). Cox regression tested the ability of individual metabolites to predict progression-free survival. Progression was defined as the time point at which the local multi-disciplinary team decided to further treat the tumour. Low normalised tissue glutamine concentration was found to be associated with a worse progression-free survival (HR=4.58; P<0.05). Glutamine was found to significantly negatively correlate with glutamate (R 2 =-0.48; P<0.05), suggesting a metabolic link between the metabolites and a mechanism for low glutamine in high-risk tumours. Greater post-surgical residual was associated with poorer progression-free survival (log-rank P<0.05) in this cohort; however, there was no significant correlation between the size of residual tumour and glutamine. This study has shown that metabolite concentrations obtained from tissue samples are associated with progression-free survival of cerebellar pilocytic astrocytoma patients. Low glutamine has previously been associated with worse overall survival in children's brain tumours. Knowledge of a high risk of progression may have altered the clinical management of one patient in our cohort with disease progression. HR-MAS acquires data in minutes and could detect high-risk tumours intraoperatively.